PEMBINAAN KELUARGA SAKINAH TERHADAP PREVENTIF PERCERAIAN DI KANTOR URUSAN AGAMA KECAMATAN SOMBA OPU KABUPATEN GOWA - AB, Syamsuddin; Arianti, Isma (Jurnal Berita Sosial, 2019)
Sakinah family coaching towards divorce prevention aims to foster family sakinah against pre-marital divorce prevention and to find out the inhibiting and supporting factors in sakinah family coaching towards preventive pre-marital divorce. This study uses a qualitative descriptive approach. The subject of the study was the coach of the sakinah family in the Office of Religious Affairs in Somba Opu District, Gowa Regency. Data collection uses structured and unstructured interview observation methods, as well as documentation. The author conducts research assisted with interview guidelines, observation guidelines. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The results showed that: 1). The form of sakinah family coaching to prevent pre-marital divorce in the Office of Religious Affairs in Somba Opu District, Gowa Regency is face to face, groups, lectures and discussions. In conducting the training for the participants the instructor / functional instructor gives advice in the form of family secrets, 2). The inhibiting factor in the formation of a Sakinah family towards the prevention of premarital divorce is work and misunderstanding for some people regarding the formation of a Sakinah family. Supporting factors are human resources, facilities and the number of places of worship.